Sunn hemp (Crotalaria juncea L.): A summer cover crop for Florida vegetable producers: HS1126/HS376, 1/2008 - Treadwell, Danielle D.; Alligood, Mike (EDIS, 2008)
HS1126, a 6-page illustrated fact sheet by Danielle D. Treadwell and Mike Alligood, summarizes the recommended cultural practices to help vegetable growers grow a successful summer cover crop and to optimize the amount of nitrogen that is returned to a vegetable crop. Includes references. Published by the UF Department of Horticultural Sciences, January 2008.